2015
DOI: 10.4103/0366-6999.149190
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Renal Oncocytoma and Renal Clear Cell Carcinoma Using Relative CT Enhancement Ratio

Abstract: Background:The difference between renal oncocytomas (RO) and renal clear cell carcinomas (RCCs) presents the greatest diagnostic challenge. The aim of this study was to retrospectively determine if RO and RCCs could be differentiated on computed tomography (CT) images on the basis of their enhancement patterns with a new enhancement correcting method.Methods:Forty-six patients with a solitary renal mass who underwent total or partial nephrectomy were included in this study. Fourteen of those were RO and 32 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 23 publications
3
21
1
Order By: Relevance
“…[1315161832] Among RCCs, a central stellate scar appeared to be an exclusive feature of the chromophobe subtype although it may also be found in oncocytoma. [192021] All cases involving a central stellate scar on imaging were confirmed histologically.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[1315161832] Among RCCs, a central stellate scar appeared to be an exclusive feature of the chromophobe subtype although it may also be found in oncocytoma. [192021] All cases involving a central stellate scar on imaging were confirmed histologically.…”
Section: Discussionmentioning
confidence: 98%
“…[18] Spoke-wheel enhancement and a central stellate scar – imaging findings initially observed in oncocytomas have recently been recognized in chromophobe RCCs as well. [192021] Several studies evaluated the degree of RCC enhancement subjectively and quantitatively[13222324252627] while others correlated magnetic resonance imaging (MRI) findings such as diffusion-weighted imaging (DWI) and apparent diffusion coefficient (ADC) values, with the RCC subtype. [28293031] Thus, the objectives of this present study were: (1) to define the characteristic imaging appearances of the various RCC subtypes including quantifying the degree of tumor enhancement, (2) to integrate the imaging findings with relevant demographic and clinical parameters, and (3) to frame the results of this study in the context of the existing literature.…”
Section: Introductionmentioning
confidence: 99%
“…If the blood supply of tumour and blood loss can be reduced, the operation will be more calm and safe. The CT enhancement rate can reflect on blood supply of tumour and even suggest the characteristic and prognosis of some tumours [21], [22]. The CT value of the same lesion areas were measured before and after treatment in the same CT machine.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, McGahan et al found the presence of segmental enhancement inversion pattern in only one of 16 small ROs (24). In the study by Ren et al, no tumors showed distinct segmental enhancement inversion (25).…”
Section: Discussionmentioning
confidence: 94%